We can’t afford the candy! The influence of parenting by lying about money on mobile phone addiction and the roles of anxiety and socioeconomic status among Chinese adolescents - Wei, Hua; Lu, Lijun; Liu, Meiting (Frontiers in Psychology, 2022)
Extant research has indicated that parenting practice, such as harsh parenting, rejection, and neglect increases the risk of mobile phone addiction. However, no research to date has examined the association between parenting by lying about money and adolescent mobile phone addiction. Objective: The current study used a survey to test whether parenting by lying about money may be associated with adolescent mobile phone addiction. The mediation of anxiety and moderation of socioeconomic status were also examined. Methods: We recruited 971 adolescents from five secondary schools in a city in central China. Of the participants, 448 (46.14 %) were boys and 523 (53.86 %) were girls (M age = 13.63, SD age = 1.01). Results: The results of mediation analysis indicated that parenting by lying about money positively predicted mobile phone addiction (B = 0.144, p < 0.01); parenting by lying about money positively predicted anxiety (B = 0.126, p < .01) and mobile phone addiction (B = 0.107, p < 0.01). Anxiety positively predicted mobile phone addiction (B = 0.293, p < 0.01). Moreover, the bias-corrected bootstrapping mediation test indicated that the process by which parenting by lying about money predicted mobile phone addiction through anxiety was significant (indirect effect = 0.037, SE = 0.011, 95% CI = [0.017, 0.059]). Conclusions: The current study suggests that parenting by lying about money may lead to mobile phone addiction through the mediation of anxiety. However, the effect was stronger for adolescents with higher level of socioeconomic status than their counterparts.